Analisis HOTS Buku Teks Rancagé Diajar Basa Sunda Kelas VII SMP Kurikulum Merdeka - Rinrin Nurlela; Usep Kuswari; Haris Santosa Nugraha (Jurnal Ilmiah Global Education, 2026)
The implementation of the Merdeka Curriculum demands a transformation of instructional materials capable of systematically stimulating students' critical thinking skills; however, the integration of Higher Order Thinking Skills (HOTS) in regional language textbooks tends to be limited compared to national subjects. This study aims to describe the distribution of HOTS, the variation of HOTS operational verbs, and the types of stimuli used in the Seventh-Grade Sundanese textbook Rancagé Diajar Basa Sunda. The novelty of this study lies in its focus on the analysis of HOTS implementation within Sundanese local content, which remains under-researched, compared to national subjects. Using a qualitative approach with a descriptive method through content analysis techniques, this study employed the Revised Bloom's Taxonomy as the research instrument to dissect cognitive levels. A total of 294 content units were collected through documentation techniques, while data validity was ensured through theory triangulation to maintain the objectivity of the analysis. The results reveal that only 98 items (33%) meet the HOTS criteria, while the majority, comprising 196 items (67%), remain at the Lower Order Thinking Skills (LOTS) level. Although the C4 (analyzing) level is predominant, the C5 (evaluating) and C6 (creating) levels occur with minimal frequency, supported by stimuli restricted to simple discourse texts. These findings confirm that the HOTS content in the textbook has not yet reached the ideal standard of 40–60%. The implications suggest that textbook authors must reconstruct materials by enriching visual stimuli and problem-based tasks to transform Sundanese language learning from mere linguistic mastery into the development of cognitive competencies relevant to 21st-century educational needs.